The Prevalence and Predictive Factors of Genitourinary Syndrome of Menopause in Postmenopausal Women: A Cross-sectional Study - Azamsadat Mahmoudian; Zohre Zamani; Fatemeh Mohammadzadeh; Narjes Bahri (International Journal of Community Based Nursing and Midwifery)
Background: Genitourinary Syndrome of Menopause (GSM) refers to signs and symptoms caused by estrogen deficiency in the genitourinary system. Given the importance of GSM in women’s health during menopause, the present study was designed to determine its prevalence and predict factors for postmenopausal women in Gonabad City.Methods: This cross-sectional-analytical study was conducted on 455 postmenopausal women (45-75 years old) referring to three Comprehensive Health Service Centers in Gonabad City, Iran, from September 2021 to July 2022. A stratified random sampling method was applied. Demographic and reproductive questionnaire, urogenital complaints checklist, the Day-to-Day Impact of Vaginal Aging (DIVA) questionnaire, and vaginal examination were used to collect the data. Data were analyzed using the SPSS software version 16.0 using descriptive statistics and independent t-test, Mann-Whitney test, chi-square test, and logistic regression models at the significance level of P<0.05.Results: Of the 455 participants, 238 (52.3%) had GSM. The most common complaints among the participants were urinary incontinence, which was present in 179 (39.34%) participants, and dyspareunia, which was present in 94 (20.66%) participants. Women in the GSM group reported a higher prevalence of dysuria, urinary frequency, urgency, and incontinence, as well as dyspareunia, postcoital bleeding, vaginal dryness, vulvar irritation, and vulvar burning or itching compared to the non-GSM group (P<0.001). Age (P=0.025), gravida (P=0.018), and urinary problems (P<0.001) were predictive factors for GSM.Conclusions: The prevalence of GSM was remarkable in postmenopausal women in Gonabad. Identifying age, gravida, and urinary problems as key predictors of GSM highlights the importance of early screening and tailored management strategies for at-risk populations.